2006
DOI: 10.1007/s10573-006-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Aluminum with Detonation Products

Abstract: A method of electrical conductivity and an analysis of recovered explosion products are used to study interaction of aluminum with detonation products of condensed high explosives. The electrical conductivity of HMX/Al and RDX/Al mixtures is inhomogeneous; a region with the maximum electrical conductivity is adjacent to the detonation front, whereas the electrical conductivity decreases with distance from the front. If the wave is incident onto a wall, the electrical resistance of the composite high explosive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Des- tex is a TNT based aluminized composite explosive. Aluminized explosives are classified as having nonideal behavior [16,20]. In such materials, the metal additive reacts with the detonation products expanding behind the detonation zone [16,20].…”
Section: Effect Of Mist On Blastmentioning
confidence: 99%
See 1 more Smart Citation
“…Des- tex is a TNT based aluminized composite explosive. Aluminized explosives are classified as having nonideal behavior [16,20]. In such materials, the metal additive reacts with the detonation products expanding behind the detonation zone [16,20].…”
Section: Effect Of Mist On Blastmentioning
confidence: 99%
“…Aluminized explosives are classified as having nonideal behavior [16,20]. In such materials, the metal additive reacts with the detonation products expanding behind the detonation zone [16,20]. This causes an increase in temperatures and pressures associated with the blast, and as a result, the addition of aluminum powder has traditionally been used in military applications.…”
Section: Effect Of Mist On Blastmentioning
confidence: 99%
“…The effect of the aluminum content in condensed high explosives (HEs) has been studied in some detail [14,[18][19][20][21][22][23]. However, the precise influence of aluminum on shock dynamics is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that its influence is limited to short time scales, preferably in the presence of oxygen, if it is to support propagation of the shock front due to the liberation of chemical energy during the reaction [21]. Gilev and Anisichkin [23] used electrical conductivity measurements during an explosion to suggest that the reaction of aluminum with detonation products occurs within a microsecond time span immediately upon detonation. Analyzing the solid residue after a detonation in an explosion chamber, they concluded that a thin oxide layer quickly formed around the aluminum particles effectively inhibits a further reaction of bulk aluminum with other species, resulting in the majority of the aluminum additive acting as inert non-participants in the detonation.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminized composite explosives are classified as having nonideal behavior [11,20]. In such materials, the metal additive reacts with the detonation products expanding behind the detonation zone [11,20].…”
Section: Destexmentioning
confidence: 99%